The new paradigm of international production: Empirical evidence of Spanish offshoring activities - David de Matías Batalla (Kiel Institute for the World Economy (IfW), 2016)
In this paper, the author presents the impact of new players and factors in international business activities, which have a direct influence on international economic structure. One of the most important determinants over the last decades has been foreign direct investment, which has encouraged the dislocation of business activities in many industries. This, together with the rest of foreign direct investment, makes the author think of extending the OLI model to OLIM, where M is the mode of entry. One type of this mode is offshoring which makes easier the relocation of business activity from developed economies to developing economies. The study of offshoring activities is the focus of this paper, with the data coming from a survey of 166 Spanish multinational firms. Empirical evidence should provide us the main factors that motivate Spanish multinational firms to be engaged in foreign direct investment via offshoring.
Keywords: D23; F21; F23; 330; foreign direct investment; eclectic paradigm; internationalization process; offshoring; multinational firms